POST-MODERN HEALTH ECONOMY DEMAND PARADOX IN ECOMICS MODELS, EVIDENCE AFTER COVID-19 - Aveni, Alessandro (Revista JRG de Estudos Acadêmicos, 2020)
The paper seeks determinants of health demand using the economic analysis in order to clarify what could change after the market failures due to the Covid-19 pandemic during 2020. The economic models stated that the increase in public spending on health and in universal health systems had positive impacts on the economy of health and in general on collective health. This is a paradox because the opposite have been occurred in all economy and all over the world. Exploring the determinants of demand with bibliographic evidences form economic theories, the paper point out elements of reflection on what should be considered the demand for health for the public and private health. The results of the paper explain such paradox and underline the real demand determinants that must be assessed. The paper allows us to think how to overcome the past centuries health paradigm centered on offering medical assistance to the population through controlled markets, public health systems and the “health demand” assessment considering health as a capital good. The finals remarks of the paper could be used as a bridge to a postmodern health evaluation centered on the human being and not as an asset.